Indigenous Peoples, Social Movements, and the Legacy of Hugo Chávez's Governments. (January 2017) - Angosto-Ferrández, Luis F.
The unprecedented enfranchisement of Venezuela's indigenous population is partly a result of the formation of a state-sponsored indigenous movement. This movement prioritizes access to social services, economic development, and political participation in state structures over certain goals of free determination. Other forms of collective action with different priorities are evidence of the existence of diverging interests and goals among indigenous people. These divergences are a reflection of the way in which the indigenous population partakes in the shaping of contemporary Venezuelan politics. La inclusión social de las comunidades indígenas de Venezuela no tiene precedentes y se debe, en parte, a la formación de movimientos indígenas auspiciados por el estado. Estos movimientos le dan prioridad al acceso a los servicios sociales, al desarrollo económico y a la participación política en las estructuras estatales por encima de ciertas metas de libre determinación. Otras formas de acción colectiva con prioridades diferentes revelan la presencia/existencia de intereses y objetivos divergentes entre las comunidades indígenas. Estas diferencias son un reflejo de la manera en que las poblaciones indígenas participan en la formación de la política venezolana contemporánea.